Interleaved non‐isolated DC–DC converter for ultra‐high step‐up applications. Issue 18 (17th February 2021) - Fani, Rezvan; Farshidi, Ebrahim; Adib, Ehsan; Kosarian, Abdolnabi
Abstract : This study presents a novel interleaved non‐isolated converter for ultra‐high step‐up applications. This circuit utilises coupled inductor and voltage‐lift techniques to achieve high voltage gain. In the proposed converter, the configuration of interleaved technique and winding‐cross‐coupled inductors not only reduces the input current ripple and current stress of semiconductor devices but also increases the voltage gain. Further, using voltage‐lift technique helps to reach a very high voltage conversion ratio with low turn ratio and proper duty cycle. Since the voltage stress of semiconductor devices is low enough, low on resistance switches and low voltage ultra‐fast recovery diodes are used. For this converter, high voltage gain, low conduction losses, low reverse recovery losses, high efficiency, low input current ripple, small volume and reduced cost are provided. Therefore, the proposed converter is a good choice for ultra‐high step‐up applications. The implemented 100 W laboratory prototype circuit with 18 V input voltage and unity turn ratio of coupled inductors reaches 360 V output voltage and 94.7% efficiency which validates the accuracy of theoretical analysis.